The portrayal of masculinity in Bangtan Boys clip video “DOPE” (Research, Society and Development, 2020)
The huge popularity of Korean boy bands nowadays is considered as one of the worldwide trending. Thus, the researcher take interest in Bangtan Boys’ (BTS) music video entitled DOPE. Since there is unique concept in this video, the researcher wants to know about the ideology behind the video. The focus of this study is to find the representation of masculinity in BTS’s music video entitled DOPE. Qualitative approach and television culture are applied by John Fiske to analyze the video clip. By using the concept of television culture and soft masculinity proposed by Sun Jung as the framework, it is expected to obtain the masculinity in this video. In the discussion, it focused on costumes, make-up, accessories, gesture, and expression. The results found that the masculinities in this video were constructed by hybrid ones. The representation of masculinity in Bangtan Boys entitled Dope combines the new concept of masculinity and traditional masculinity. Although, the members of BTS are using make-up and able to dance, they still embrace the concept of masculinity associated with logic, aggressive, protective, smart, and caring.